The Existence Of The Application Of Diversion As A Criminal Settlement In The Criminal Justice System - Ahmad Agusanto Neu; Fenty U. Puluhulawa; Fence M Wantu (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to analyze and examine the existence of the application of diversion in providing protection for children's rights. This research is normative juridical research, normative juridical is a statutory approach, because what will be studied are various rules of law that become the focus and central theme of a study. Legal analysis produced by a normative research using a statutory approach will produce more accurate research. Based on the results of the research obtained, the answer to the existing problem is that the application of diversion as a settlement of juvenile crimes is very important to protect children's rights and encourage restorative justice. Diversion not only avoids children from matters related to the formal legal process, but also provides an opportunity to improve social relations and restore the situation after a criminal offense. Despite challenges in its implementation, such as a lack of understanding among law enforcement and the community, successful diversion can improve children's welfare and achieve better justice goals. Therefore, further efforts are needed in socialization and education regarding diversion to ensure its effective implementation in the criminal justice system.